Chronic Inflammatory Demyelinating Polyradiculoneuropathy: From Bench to Bedside - Peltier, Amanda C.; Donofrio, Peter D. (Seminars in Neurology, 2012)
Chronic inflammatory demyelinating polyradiculoneuropathy (CIDP) is the most common treatable chronic autoimmune neuropathy. Multiple diagnostic criteria have been established, with the primary goal of identifying neurophysiologic hallmarks of acquired demyelination. Treatment modalities have expanded to include numerous immunomodulatory therapies, although the best evidence continues to be for corticosteroids, plasma exchange, and intravenous immunoglobulin (IVIg). This review describes the pathology, epidemiology, pathogenesis, diagnosis, and treatment of CIDP.
Keywords: CIDP; demyelination; inflammatory neuropathy